A national survey assessing the number of records allowed open in electronic health records at hospitals and ambulatory sites. (17th April 2017) - Adelman, Jason S; Berger, Matthew A; Rai, Amisha; Galanter, William L; Lambert, Bruce L; Schiff, Gordon D; Vawdrey, David K; Green, Robert A; Salmasian, Hojjat; Koppel, Ross; Schechter, Clyde B; Applebaum, Jo R; et al.
Abstract: To reduce the risk of wrong-patient errors, safety experts recommend limiting the number of patient records providers can open at once in electronic health records (EHRs). However, it is unknown whether health care organizations follow this recommendation or what rationales drive their decisions. To address this gap, we conducted an electronic survey via 2 national listservs. Among 167 inpatient and outpatient study facilities using EHR systems designed to open multiple records at once, 44.3% were configured to allow ≥3 records open at once (unrestricted), 38.3% allowed only 1 record open (restricted), and 17.4% allowed 2 records open (hedged). Decision-making centered on efforts to balance safety and efficiency, but there was disagreement among organizations about how to achieve that balance. Results demonstrate no consensus on the number of records to be allowed open at once in EHRs. Rigorous studies are needed to determine the optimal number of records that balances safety and efficiency.